Ubiquitin-mediated receptor degradation contributes to development of tolerance to MrgC agonist–induced pain inhibition in neuropathic rats. Issue 4 (April 2021) - Huang, Qian; Ford, Neil C.; Gao, Xinyan; Chen, Zhiyong; Guo, Ruijuan; Raja, Srinivasa N.; Guan, Yun; He, Shaoqiu
Abstract : Abstract: Agonists to subtype C of the Mas-related G-protein-coupled receptors (MrgC) induce pain inhibition after intrathecal (i.t.) administration in rodent models of nerve injury. Here, we investigated whether tolerance develops after repeated MrgC agonist treatments and examined the underlying mechanisms. In animal behavior studies conducted in male rats at 4 to 5 weeks after an L5 spinal nerve ligation (SNL), the ability of dipeptide MrgC agonist JHU58 (0.1 mM, 10 μL, i.t.) to inhibit mechanical and heat hypersensitivity decreased after 3 days of treatment with a tolerance-inducing dose (0.5 mM, 10 μL, i.t., twice/day). In HEK293T cells, acute treatment with JHU58 or BAM8-22 (a large peptide MrgC agonist) led to MrgC endocytosis from the cell membrane and later sorting to the membrane for reinsertion. However, chronic exposure to JHU58 increased the coupling of MrgC to β-arrestin-2 and led to the ubiquitination and degradation of MrgC. Importantly, pretreatment with TAK-243 (0.2 mM, 5 μL, i.t.), a small-molecule inhibitor of the ubiquitin-activating enzyme, during tolerance induction attenuated the development of tolerance to JHU58-induced inhibition of mechanical and heat hypersensitivity in SNL rats. Interestingly, morphine analgesia was also decreased in SNL rats that had become tolerant to JHU58, suggesting a cross-tolerance. Furthermore, i.t. pretreatment with TAK-243, which reduced JHU58 tolerance, also attenuated the cross-tolerance to morphine analgesia. These findings suggest that tolerance can develop to MrgC agonist–induced pain inhibition after repeated i.t. administrations. This tolerance development to JHU58 may involve increased coupling of MrgC to β-arrestin-2 and ubiquitin-mediated receptor degradation. Abstract : Supplemental Digital Content is Available in the Text.This study shows that repeated intrathecal administrations of JHU58 lead to development of tolerance. Treatment with an inhibitor of the ubiquitin-activating enzyme during tolerance induction reduces JHU58 tolerance.